Serum lipids and smoking status in coronary heart disease patients treated with simvastatin - L. R. Gazdanova; V. A. Metelskaya; I. E. Koltunov; N. M. Akhmedzhanov; E. B. Yarovaya (Кардиоваскулярная терапия и профилактика, 2010)
Aim. To study the effectiveness of generic simvastatin in hyperlipidaemia (HLP) correction (isolated hypercholesterolemia, HCH, or HCH combined with hypertriglyceridemia, HTG) in patients with confirmed diagnosis of coronary heart disease (CHD), in regard to their smoking status. Material and methods. In total, 43 CHD patients with HLP (22 men and 21 women) were divided into two groups: never-smokers (n=22) and smokers (n=21). All patients received generic simvastatin (40 mg/d) for 12 weeks. Results. The dynamics of lipid-lowering effect of simvastatin was more manifested in the first 6 weeks of the therapy, regardless of smoking status of CHD patients with HLP. However, in non-smoking individuals, this effect was stronger. Smoking restricted lipid-lowering activity of generic simvastatin, which was manifested in smaller reduction in total cholesterol (TCH) levels, lower percentage of patients achieving target TCH concentration, and unchanged TG levels in the first 6 weeks among smokers, in contrast to a significant triglyceride-lowering effect in non-smokers. According to veloergometry results, generic simvastatin therapy was associated with increased physical stress tolerability in both groups, with a tendency towards increased peak oxygen uptake in smokers. Conclusion. Generic simvastatin (40 mg/d) was as effective in HLP correction as original statins, being less expensive than the latter. Generic simvastatin therapy could neutralise adverse effects of smoking on blood lipids. Therefore, generic statins could be used in many CHD patients who cannot afford buying original statins.